2022
DOI: 10.5334/dsj-2022-013
|View full text |Cite
|
Sign up to set email alerts
|

Development and Governance of FAIR Thresholds for a Data Federation

Abstract: The FAIR (findable, accessible, interoperable, and re-usable) principles and practice recommendations provide high level guidance and recommendations that are not research-domain specific in nature. There remains a gap in practice at the data provider and domain scientist level demonstrating how the FAIR principles can be applied beyond a set of generalist guidelines to meet the needs of a specific domain community.We present our insights developing FAIR thresholds in a domain specific context for self-governa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…During the development of the minimum thresholds for AgReFed, exemplar datasets were initially found to vary in findability, that is, whether they had a permanent identifier, a metadata record and whether that metadata record was indexed in a searchable repository (Wong et al 2022). Fully automated assessment tools are unable to capture any FAIR metrics in scenarios where a dataset doesn't at least have a Uniform Resource Locator (URL) and a machinereadable metadata record.…”
Section: Limitations Of Existing Fair Assessment Toolsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the development of the minimum thresholds for AgReFed, exemplar datasets were initially found to vary in findability, that is, whether they had a permanent identifier, a metadata record and whether that metadata record was indexed in a searchable repository (Wong et al 2022). Fully automated assessment tools are unable to capture any FAIR metrics in scenarios where a dataset doesn't at least have a Uniform Resource Locator (URL) and a machinereadable metadata record.…”
Section: Limitations Of Existing Fair Assessment Toolsmentioning
confidence: 99%
“…AgReFed's common vision is to 'enable Findable, Accessible, Interoperable and Reusable (FAIR) agricultural data to accelerate innovation and increase the profitability and sustainability of Australian agriculture' (Agricultural Research Federation 2023). The AgReFed community developed a domain-specific FAIR assessment that defines thresholds based on minimum standards, acceptable standards and stretch goals (Wong et al 2022). AgReFed recognises that FAIR is a journey that is supported through education and tooling (Mons et al 2020;Devaraju et al 2021) and that FAIR assessments are among the tools and technologies that assist with the provision of FAIR data (Krans et al 2022;Thompson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Admirably, over the past 20 years, data science organizations and journals have drawn attention to social barriers to data sharing, such as differing incentive structures and levels of training within and across diverse disciplinary communities, scholarly generations, and geographic boundaries (Borgman 2012;Gownaris et al 2022;Laine 2017;van Panhuis et al 2014). Research examining how to support the uptake of best practices, such as FAIR (findable, accessible, interoperable, and reusable) guidelines and data management planning, has shown that adoption not only depends on clear guidance and welldesigned infrastructure but also social advocacy, relationship building, and an amenable financial, legal, and policy landscape (Wong et al 2022). Movements to prioritize the rights and interests of Indigenous peoples in the knowledge economy have highlighted the need for alternative data governance models that privilege self-determination and collective benefits (Carroll et al 2020).…”
Section: Where Are the 'Social' And The 'Cultural' In Data Science Di...mentioning
confidence: 99%